EFFECS OF CONGENITAL DISORDERS OF BODY DEVELOPMENT ON MOTOR FUNCTION OF ATHLETES FROM ADAPTIVE SPORTS - Fedulova, D.V.; Serova, N.B.; Barbas, I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze the relationship between stable health disorders and motor asymmetry in the lower limbs of athletes from adaptive track and field. Methods and structure of the study. During the study, three stable disorders in track and field athletes were analyzed: intellectual disability, hearing impairment, cerebral palsy. The study involved 21 track and field athletes with disabilities having the sports qualifications from I adult category to Master of Sport of Russia. All athletes performed in the sprint and middle-distance running discipline. The athletes were divided into groups based on the degree of health impairment. The study was conducted on the basis of the State Autonomous Institution "Sports adaptive school" of the Sverdlovsk region using the Humac Norm multifunctional simulator. The athletes were subjected to testing of the anterior and posterior thigh muscles and internal and external tibial muscles in the concentric and eccentric modes of muscle activity.